PENGARUH KOMPOSISI DOSIS PUPUK UREA, SP-36, KCL DAN PUPUK ORGANIK CAIR NASA TERHADAP HASIL TANAMAN BAWANG MERAH (Allium cepa fa. ascalonicum, L.) - Yuli Widiastutik; Hadi Rianto; Historiawati Historiawati (JURNAL VIGOR, 2018)
A research studied the effect of dose of Urea, SP-36, KCl and Nasa organic liquid fertilizer on onion (Allium cepa fa. ascalonicum, L.) yield. The research has been conducted on May 2017 to August 2017 in Sawangan, Magelang. The altitude is 485 m, the soils regosol with pH of 5.5. This study uses factorial experiment (3 x 3) arranged in a complete randomized block design with three blocks. The first factor is dose of Urea, SP-36, KCl, 95 kg Urea/ha, 46 kg SP-36/ha, 60 kg KCl/ha, 190 kg Urea/ha, 92 kg SP-36/ha, 120 kg KCl/ha, and 285 kg Urea/ha, 138 kg SP-36/ha, 180 kg KCl/ha. The second factor is Nasa organic liquid dose, 2, 3 and 4 ml nasa/l. The result of the research shows that dose 285 kg Urea/ha, 138 kg SP-36/ha, 180 kg KCl/ha increase the number of leaves, number of bulbs per hill, fresh weight of bulbs per hill, fresh weight of bulbs per plot and weight of dry stored bulbs per plot. Nasa organic liquid dose 3 ml nasa/l water can increase height of plant, the leaves long, number of leaves, number of bulbs per clump, fresh weight of bulbs per clump, weight of dry saved bulbs per clump, fresh weight of bulbs per plot and weight of dry bulbs per plot. Onion plant shows the same response on dose Urea, SP-36, KCl and Nasa organic liquid in all observation parameter except fresh weight of bulbs per hill and weight of dry stored bulbs per hill.